Optimization Of Abrasive Waterjet Machining Process Parameters Using Orthoganalarray With Grey Relational Analysis - Azmir, Azhari; A. A., Aziz; M. M., Noor (2007)
In the present work, the optimization of the abrasive water jet machining (AWJM) process parameters with multiple performance characteristics based on the orthogonal array with the grey relational analysis (GRA) has been studied. Optimization of multiple response characteristics is far more complex compared to optimization of single performance characteristic. A grey relational grade (GRG) calculated based on grey relational analysis is used to optimize the AWJM process with the multiple performance characteristics. In the present study, four machining parameters, namely hydraulic pressure, abrasive mass flow rate, standoff distance and traverse rate are optimized with consideration of multiple performance characteristics viz., surface waviness at four different heights of a Kevlar composite laminate. Experimental results have shown that machining performance in the AWJM process can be improved effectively using this approach.